Pengaruh Terpaan K-Drama terhadap Perilaku Meniru Mahasiswa Semester 5 KPI IAIN Parepare - Rizky Binti Kisman; Nurhakki Nurhakki (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
Korean dramas, a production of television series from Korea, have gained significant popularity in Indonesia. This is due to the fact that Korean dramas provide substantial inspiration, particularly regarding the lifestyle and fashion trends among young people. The purpose of this research is to examine whether exposure to Korean dramas influences the imitation behavior of 5th-semester KPI students at IAIN Parepare. The research sample was selected using the purposive sampling technique. The research employed a quantitative approach through a survey method, and the data were analyzed using SPSS (Statistical Package for the Social Sciences) version 22. The research results indicate that there is an influence between the variable of K-drama exposure and the imitation behavior of 5th-semester KPI students at IAIN Parepare (p-value = 0.002 < 0.05).